2022
DOI: 10.3389/fimmu.2022.885609
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and Yang of IL-17 in Systemic Sclerosis

Abstract: IL-17 (IL-17A) is a pro-inflammatory cytokine produced by a sub-set of T helper cells termed Th17 cells primarily in response to cytokines like TGF-β and IL-23 and play an important role in host defense. IL-17 signals via the IL-17RA/RC heterodimer and the adaptor protein Act1 to activate both canonical and non-canonical pathways inducing transcriptional activation and stabilization of mRNAs. IL-17 appears to act not directly on immune cells but stimulates stromal cells such as endothelial and epithelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
1
20
0
2
Order By: Relevance
“…This finding is of general interest since Th17 cells appear to play important roles in many autoimmune diseases (57, 58). In SSc, several studies indicate key roles of Th17 cells in disease pathogenesis, but the mechanism by which these cells operate have still not been fully worked out (59)(60)(61). Regarding SSc-PAH, data are limited, but there is one study indicating Th17 polarization by flow cytometry of lymphocytes from PAH patients (62).…”
Section: B Amentioning
confidence: 99%
“…This finding is of general interest since Th17 cells appear to play important roles in many autoimmune diseases (57, 58). In SSc, several studies indicate key roles of Th17 cells in disease pathogenesis, but the mechanism by which these cells operate have still not been fully worked out (59)(60)(61). Regarding SSc-PAH, data are limited, but there is one study indicating Th17 polarization by flow cytometry of lymphocytes from PAH patients (62).…”
Section: B Amentioning
confidence: 99%
“…Among the six members of the IL-17 cytokine family (IL-17A-F), IL-17A is the pioneer cytokine mostly studied in Th17 immunopathogenesis of SSc. 58,59 Th17 cells predominantly secrete IL-17A and IL-17F, but their response is skewed toward the IL-17A pathway than the IL-17F pathway. 59 Nakashima et al first observed no increase in IL-17F levels in the sera of patients with SSc.…”
Section: Il-17amentioning
confidence: 99%
“…58,59 Th17 cells predominantly secrete IL-17A and IL-17F, but their response is skewed toward the IL-17A pathway than the IL-17F pathway. 59 Nakashima et al first observed no increase in IL-17F levels in the sera of patients with SSc. However, a proportional increase in the IL-17F population with disease duration and severity has also been reported.…”
Section: Il-17amentioning
confidence: 99%
See 2 more Smart Citations